La madona de Notre-Dame - Ragougneau, Alexis, 1973- (Nuevos tiempos (Madrid, Spain), 2014)
Commander Landard, Lieutenant Gombrowicz, and prosecutor Claire Kauffman investigate a holy terror when a lavishly-dressed woman's dead body is found next to a statue of the Virgin Mary in a Notre-Dame cathedral. Nuevos tiempos (Ediciones Siruela) series, 280pp.